HIV stories : the archaeology of AIDS writing in France, 1985-1988 - Boulé, Jean-Pierre (Liverpool Science Fiction Texts., 2002)
This book draws attention to the existence in France of an AIDS literature from 1985 to 1988 before AIDS writing became either a widely recognised genre or a culturally influential form of writing. It is a predominantly literary critical study, informed by gender studies and psychoanalytic criticism in its readings of individual texts, and interwoven with contextual information.